Seeing the Unobservable from the Invisible: The Role of CO2 in Measuring Consumption Risk - Chen, Zhuo; Lu, Andrea (Review of Finance, 2018)
Abstract In contrast to past studies that assume service flow of durable goods consumption to be a constant fraction of the stock, we study a consumption-based asset pricing model featuring time-varying utilization of durable goods. We propose an innovative measure of the unobserved usage of durable goods from carbon dioxide emissions. We find that the time-varying utilization of durable goods is a valid pricing factor. Our model exhibits a stronger cross-sectional pricing power than several consumption-based capital asset pricing models, including Yogo’s (2006) durable goods model. Finally, our model mitigates the joint risk premium and implied risk-free rate puzzle.